In memoriam - prof. Krzysztof Marasek (1958-2019) - Ryszard GUBRYNOWICZ (Archives of Acoustics, 2020)
Krzysztof Marasek, lecturer and researcher at the Polish-Japanese Academy of Information Technology (PJAIT) and an expert at the National Information Processing Institute (OPI PIB) passed away on November 13, 2019. He was an outstanding scientist, an internationally acclaimed authority in the field of speech technology, an outstanding academic teacher and mentor to many scientists at home and abroad. Professor Krzysztof Marasek headed the PJAIT Multimedia Department created by him in 2002.